Determining the Median Lethal Concentration (LC50) and Seedling Growth Effects of MARDI Nano-fertilizer on Rock melon (Cucumis melo) (Asian Journal of Plant Biology, 2023)
New fertilizer formulations and nitrogen delivery systems are needed to address deteriorating nutrient-use-efficiency and environmental hazards due to farmers' dependency on chemical fertilizers. Nanofertilizers (NF) made from tailored smart nano materials are a viable alternative to inefficient and harmful traditional fertilizers. Nanotechnology and NFs may help solve chemical fertilizers formulation difficulties. To boost rock melon yields, MARDI has created a nano-fertilizer made from nano-emulsions. The relations between seed germination inhibition (%) of rock melon seed and different concentrations of MARDI nano-fertilizer showed that when nano-fertilizer concentrations increased from 10 to 45% with inhibition 3.3% to 100%, seed germination decreased. The LC50 value was calculated at 32.2% equal to 322,000 ppm, with upper and lower limits at 25.346% and 40.953%, 96 hrs after treatments, indicating the formulation is not toxic with a high LC50 value. In order to further study the effects of the created nano-fertilizer on the growth of rock melon plants across the adult, reproductive, and developmental stages, it is suggested that future field trials work use a concentration of 0.5% of the developed MARDI nano-fertilizer.
Keywords: Nano-emulsion; Nano-fertilizer; Rock melon; LC50; Toxicity